Myopia and saliency in renewable resource management. (23rd April 2018) - Gregg, Daniel; Rolfe, John
Abstract : An important challenge in managing renewable resources is to understand why owners and managers sometimes make decisions that deplete resources and future earnings, such as when graziers allow pastures and land condition to be degraded. In this paper, we test two potential reasons for unsustainable management practices, myopia and salience, with each explaining why resource managers may exhibit impatience in harvest decisions. Myopia is associated with decision makers placing lower weight on future outcomes than would be implied by their pure time preference. Salience is associated with overweighting of consumption 'now', implying inconsistency in time preferences. To test for these effects on renewable resource management, an incentivised, dynamic field experiment was carried out with rangeland grazing enterprise owners in north‐eastern Australia that related management choices with uncertain rainfall events to both profits and land condition over time. Results demonstrate that respondents exhibiting myopia/salience in their choices tended to achieve lower cumulative scores in the experiment, as well as lower land conditions on their properties as measured with remote sensing data. Our results explain why there may be persistent optimisation failures by resource owners that reduce both profits and environmental outcomes.